Diversity of mangrove vegetation and carbon sink estimation of Segara Anakan Mangrove Forest, Cilacap, Central Java, Indonesia - ANI WIDYASTUTI; EDY YANI; ERY KOLYA NASUTION; ROCHMATINO ROCHMATINO (Biodiversitas Journal of Biological Diversity, 2018)
Widyastuti A, Yani E, Nasution EK, Rochmatino. 2018. Diversity of mangrove vegetation and carbon sink estimation of Segara Anakan Mangrove Forest, Cilacap, Central Java, Indonesia. Biodiversitas 19: 246-252. Mangrove forests are known as standing stores of sequestered atmospheric carbon. The role of mangrove forests in the sequestering substantial amount of atmospheric carbon dioxide (CO2) and storing the carbon in its biomass has been recently underscored. This research aimed to estimate vegetation diversity and carbon sink potential of Segara Anakan Mangrove Forest Cilacap, Central Java from August-December 2012. Vegetations sampling was done by square plots technique. Diversity index was utilized to determine species diversity. Allometric equations were used to estimate biomass and carbon sinks. This study only calculates aboveground biomass and carbon sinks. The research results showed that mangrove in Segara Anakan was composed of 24 species with 19 families, consisting of 16 species of trees, 14 species of saplings and 16 species of herbs. The most dominant tree was Avicennia marina with importance value of 43.62% in Kembang Kuning, 60.27% in Ujung Alang and 25.6% in Klaces. The most dominant of sapling was Avicennia marina, with an important value of 31.1%. The total biomass of a tree is about 43.06 kg/tree or 0.13 ton/ha. Total biomass of sapling was 27.38 kg/tree or 0.32 ton/ha. The carbon sink of the tree was 49.10 ton/ha and carbon sink of sapling was 79.39 ton/ha. It can be concluded that Segara Anakan Mangrove forest is very important as a carbon sink in South part of Central Java, Indonesia.